Enantiopure oxazolidinones as chiral acids in the asymmetric protonation of N-Boc pyrrole derived enolates. - Carbery, DR; Donohoe, T (2004)
The first use of geminally disubstituted oxazolidinones as chiral protonating agents is described: these new acids are able to directly protonate an enolate generated by the ammonia free partial reduction of an electron deficient pyrrole and give up to 68% ee in the pyrroline product.